Isolating Proactive Slowing from Reactive Inhibitory Control in Heavy Drinkers. (1st January 2020) - Baines, Laura; Field, Matt; Christiansen, Paul; Jones, Andrew
Abstract: Background: Impaired inhibitory control is thought to contribute to alcohol (mis)use. However, current definitions of inhibitory control are over-simplified by a failure to distinguish reactive inhibitory control from proactive slowing. Objectives: To distinguish "reactive" inhibitory control and proactive slowing in heavy drinkers, and characterize associations between both constructs and individual differences in alcohol consumption. Methods: Sixty heavy drinkers completed self-reported measures of alcohol consumption, followed by two modified Stop-Signal tasks and an AX-continuous performance task in a laboratory setting. Results: Heavy drinkers demonstrated proactive slowing when inhibition was more likely but individual differences in proactive slowing and reactive stopping were unrelated to individual differences in alcohol consumption. Conclusions/Importance: Within a sample of heavy drinkers, individual differences in reactive inhibitory control and proactive slowing are unrelated to individual differences in alcohol consumption.